Incentives and Trust Are the Main Drivers of Recruiting Participants in 6 African Countries via Web-Based Environments: A Vignette Survey Experiment - Henning Silber; Björn Rohr; Jan Priebe (Journal of Medical Internet Research)
Abstract BackgroundIn-person health surveys and biomarker collections (eg, blood testing) provide crucial data to monitor and investigate progress on health outcomes in sub-Saharan Africa. Bearing in mind that administrative sampling frames are often outdated and financial resources can be limited, it is of substantial policy importance to better understand whether recruitment of individuals for in-person health data collection efforts can be accomplished via web-based environments such as social media sites. Yet, there is little methodological research on (1) the feasibility of recruitment through web-based environments and (2) the factors that drive in-person survey participation rates in sub-Saharan Africa countries. ObjectiveThis study aimed to share our experimental results on the recruitment of individuals from sub-Saharan Africa for participation in in-person, health-related surveys and biomarker collections via Facebook ads and to provide recommendations for future data collections and research. MethodsWe conducted a preregistered 2×4×4 vignette experiment to investigate people’s willingness to participate in in-person health surveys and blood tests. The experiment was part of a web survey (n≈10,600) of individuals recruited via Facebook advertisements that we conducted in early 2023 in 6 sub-Saharan Africa countries (Ghana, Kenya, Nigeria, South Africa, Tanzania, and Uganda). Based on the theories of contextual integrity, economic participation, and social exchange, three factors were varied: (1) the topic (HIV or diabetes), (2) the incentive (US $0, US $2 cash, US $2 voucher, and US $2 lottery), and (3) the sponsor (nongovernmental organization, statistical office, health ministry, or local university). ResultsOverall, we found that a majority of survey participants are willing to participate in in-person health surveys and provide biomarkers (vignette means range between 5.54 and 6.09 on a 1 to 7 scale). First, providing a financial incentive significantly increased the likelihood of being willing to participate (bPbPbPbPbPbP ConclusionsTogether, the study’s results suggest that using a web-based environment for recruiting health research participants in sub-Saharan Africa can be a viable option and emphasize the importance of adequate compensation and trust in the sponsor. The findings also indicated that several attitudinal but almost none of the sociodemographic variables are systematically related to the willingness to participate in health-related in-person data collection activities.